POTENTIAL FOR SHALE GAS PRODUCTION - Vladimir A. Vasiliev; Andrey V. Kolomiytsev; Olga Yu. Turskaya; Elena V. Belaya (Вестник Северо-Кавказского федерального университета, 2022)
The article focuses on one of the non-conventional types of gas - shale gas; there is also an evaluation of shale gas potential production and a long-term forecast for the issue.